(untitled) (Studia austriaca, 2021)
In 1947 the Russian writer Gaito Gasdanow published The Spectre of Alexander Wolf, a novel that appears to mirror various aspects of Hugo von Hofmannsthal’s Reitergeschichte [A Cavalry Tale] (1899). Although at present it cannot be philologically proved that the Reitergeschichte directly inspired Gasdanow, several striking parallels can be drawn between the two works, such as the way the themes of war and revolution are addressed, the encounter with doppelgängers, their deaths, and how the capture of the horse ultimately deals the fatal blow to both protagonists. This article examines these aspects closely by contextualizing them within the literary output and the biographies of both authors.